COVID-19 lockdowns threaten Africa’s vital informal urban food trade - Resnick, Danielle (International Food Policy Research Institute, 2020)
As COVID-19 begins its spread across Africa, concerns are growing about how the pandemic will affect the region’s already fragile food systems, especially in densely packed cities. Much of the region’s urban population works in the informal sector — many in wet markets and as street vendors — and depends on it for food, so lockdowns and other social distancing measures could pose major problems both for consumers and workers.